Pengaruh Biochar Sekam Padi dan Jarak Tanam terhadap Pertumbuhan dan Hasil Panen Mentimun (Cucumis sativus L.) - Delfim da Costa; Salensia Haryati Afonso; Julinus Jeksen (Fakultas Pertanian, Universitas Nusa Nipa, 2026)
The study aims to determine the effects of rice husk biochar (RHB) and planting distance on the growth and yield of cucumber in the rice field after the rice harvesting period in Seical village, Baucau municipality (July-November 2025). A Randomized Block Design factorial was used, with RHB as the first factor at three levels (10 t/ha, 20 t/ha, and 30 t/ha) and plant spacing as the second factor at three levels (30 cm x 40 cm, 30 cm x 60 cm, and 30 cm x 80 cm). The results showed no interaction between rice husk biochar (RHB) treatment and plant spacing with regard to growth parameters. RHB treatment had significant effect on height at two and five weeks after planting (WAP) and on number of leaves at five WAP. Plant spacing had significant effect on stem diameter at three WAP. The RHB at 30 t/ha gave the highest root length, dry root weight, and biomass per crop. Furthermore, number of fruit abortion was high at 30 t RHB/ha and 10 t RHB /ha. Less fruit abortion was obtained at 20 t RHB/ha. The biggest fruit diameter was at the large plant spacing treatments; however, the number of fruits was low, which affected cucumber productivity. Overall, the study showed that 30 t RHB/ha increased production from 3.96 to 4.75 t/ha, while 30 cm x 40 cm plant spacing increased production from 3.33 to 4.83 t/ha. Combining 30 t RHB/ha with 30 cm x 40 cm plant spacing in a rice field after rice harvesting increased cucumber yields. Further studies on RHB with inorganic fertilizers to increase cucumber yield are recommended.